Little black dress - Talley, André Leon 1949-2022 (Skira Rizzoli, 2012)
"A celebratory tribute to the iconic little black dress and its deeply resonant cultural and social significance in the modern era ... Features an impeccable group of more than 80 dresses from many of the most eminent fashion houses"...Jacket
Published on the occasion of the exhibition held at SCAD Museum of Art, Savannah College of Art and Design, September 28, 2012-January 31, 2013
Keywords: Exhibition catalogs / fast / (OCoLC)fst01424028; Pictorial works / fast / (OCoLC)fst01423874; Dresses / fast / (OCoLC)fst00897995; Fashion design / fast / (OCoLC)fst01200123; Women's clothing / fast / (OCoLC)fst01178707; Mode / gnd; Frauenkleidung / gnd; Schwarz / gnd; Dresses -- Exhibitions; Dresses -- Pictorial works; Fashion design -- Exhibitions; Fashion design -- Pictorial works; Women's clothing -- Exhibitions; Dresses; Fashion design; Women's clothing; Mode; Frauenkleidung; Schwarz; Ausstellungskatalog -- SCAD Museum of Art -- 28.09.2012-31.01.2013 -- Savannah